Effect of centrifugation on amniotic fluid phospholipid composition (Revista Española de Fisiología, 1992)
The first step in the determination of phospholipid in amniotic fluid is generally the removal of cells and debris from the fluid by centrifugation. Low-speed centrifugation of the supernatant is reported to have the same phospholipidic profile and L/S, PG/S and PI/S ratios similar to those of the uncentrifuged amniotic fluid sample. With high-speed centrifugation almost all the pulmonary surfactant seems to be recovered in pellet with the same characteristics as the uncentrifuged amniotic fluid.